HUBUNGAN MINAT BERWIRAUSAHA DENGAN NILAI PRAKTIK KERJA INDUSTRI SISWA KELAS XII TGB SMKN 2 PAYAKUMBUH TAHUN AJARAN 2017/2018 - 2074-2079. Fauzan Febrian (Universitas Negeri Padang, 2018)
Abstract—This research originated from the problem of the value of industrial work practices of relatively high students less enthusiasm for students to entrepreneurship in the field of expertise. This is influenced by internal and external factors, one of which is influenced by internal factors of interest in entrepreneurship. This study aims to see the relationship of interest in entrepreneurship with the value of industrial work practice of class XII students TGB SMKN 2 Payakumbuh academic year 2017/2017.This correlational research did not use technique sampling because all students were made object of analysis with population of all students of class XII TGB SMKN 2 Payakumbuh as many as 28 people. Data analysis techniques used are: 1) Descriptive analysis, 2) Test requirements analysis, consisting of normality test and linearity test to prove that the distribution of data derived from samples of normal and linear distributed, and 3) Hypothesis Testing.From the results of research that has been done, it can be concluded that there is a moderate and significant relationship between entrepreneurship interest with the value of Industrial Work Practice Class XII TGB SMKN 2 Payakumbuh Year of Teaching 2017/2018. This result can be proved by the correlation coefficient of 0.635, with a significance value of 0,00 < 0,05.Keywords: Interest, Entrepreneurship, Industrial Work Practice